Discovering a Reliable Heat-Shock Factor-1 Inhibitor to Treat Human Cancers: Potential Opportunity for Phytochemists - Velayutham, Murugesan; Cardounel, Arturo J.; Liu, Zhenguo; Ilangovan, Govindasamy (Frontiers in Oncology, 2018)
Heat shock factor-1 (HSF-1) is an important transcription factor that regulates pathogenesis of many human diseases through its extensive transcriptional regulation. Especially it shows pleiotropic effects in human cancer, and hence it has recently received increased attention of cancer researchers. After myriad investigations on HSF-1, the field has advanced to the phase where there is consensus that finding a potent and selective pharmacological inhibitor for this transcription factor will be a major break-through in the treatment of various human cancers. Presently, all reported inhibitors have their limitations, made evident at different stages of clinical trials. This brief account summarizes the advances with tested natural products as HSF-1 inhibitors, and highlights the necessity of phytochemistry in this endeavor of discovering a potent pharmacological HSF-1 inhibitor.